A comparison of trends in the incidence of non-alcoholic steatohepatitis-related liver cancer in the BRICS countries from 1990 to 2021, alongside projections for the next 15 years - Chen, Congjie; Huang, Siying; Wu, Huiqiang; Hu, Weitao; Li, Chaowei; Du, Dongwei; Fang, Taiyong (Frontiers in Oncology, 2025)
BackgroundDespite the ongoing rise in the global burden of non-alcoholic steatohepatitis-related liver cancer (NALC), systematic analyses and long-term trend projections of the disease’s burden in the BRICS countries (Brazil, Russia Federation, India, China, and South Africa) remain relatively scarce.ObjectiveThe objective of this study was to systematically assess the incidence dynamics of NALC in the BRICS countries during the period from 1990 to 2021 to reveal its epidemiological characteristics, to assess the potential public health challenges, and to forecast the development trends over the next 15 years.MethodsThe present study collated and systematized the incidence data of NALC in the BRICS countries from 1990 to 2021, drawing upon the global burden of disease database (2021). The indicators that were analyzed included the incidence rate, the age-standardized incidence rate, the annual percentage change, and the average annual percentage change. The analysis incorporated the utilization of two distinct models: the joinpoint regression model and the age–period–cohort model. These models were employed to evaluate the temporal effects and population characteristics. Additionally, the autoregressive integrated moving average model was implemented to offer insights into the potential future risk of the disease.ResultsFrom 1990 to 2021, the incidence of NALC in the BRICS countries demonstrated a marked increase. The incidence rate in China exhibited an increase from 0.34 (95% uncertainty interval (UI): 0.28–0.42) to 0.79 (95% UI: 0.61–1.01). Brazil demonstrated a rise from 0.07 (95% UI: 0.06–0.08) to 0.17 (95% UI: 0.15–0.20). The Russian Federation demonstrated a rise from 0.14 (95% UI: 0.12–0.16) to 0.39 (95% UI: 0.33–0.45). India demonstrated a rise from 0.13 (95% UI: 0.10–0.16) to 0.32 (95% UI: 0.26–0.38). South Africa demonstrated a rise from 0.29 (95% UI: 0.18–0.47) to 0.74 (95% UI: 0.59–0.89). The sex analysis demonstrated that, in the majority of countries except India, the male incidence rate exhibited a higher rate of increase than the female incidence rate. The steepest age-specific increase occurred in the oldest cohorts, notably 90+ years. The predictions derived from the autoregressive integrated moving average model indicate that the prevalence of NALC morbidity is anticipated to escalate in the BRICS nations over the ensuing 15-year period.ConclusionThe present study reveals a sustained upward trend in NALC incidence in the BRICS countries during 1990–2021 and significant differences in the pace and drivers of growth across countries. The heterogeneity reflected by the joinpoint and APC models reveals gaps in the burden of metabolic diseases, public health response, and policy implementation across countries. In order to address this challenge, priority should be given to the promotion of metabolic disease-related early screening, health behavior interventions, and systematic management.